2023
DOI: 10.3390/biomedicines11030678
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming EGFR Resistance in Metastatic Colorectal Cancer Using Vitamin C: A Review

Abstract: Targeted monoclonal antibody therapy against Epidermal Growth Factor Receptor (EGFR) is a leading treatment modality against metastatic colorectal cancer (mCRC). However, with the emergence of KRAS and BRAF mutations, resistance was inevitable. Cells harboring these mutations overexpress Glucose Transporter 1 (GLUT1) and sodium-dependent vitamin C transporter 2 (SVCT2), which enables intracellular vitamin C transport, leading to reactive oxygen species generation and finally cell death. Therefore, high dose vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
(67 reference statements)
0
3
0
Order By: Relevance
“…EGFR-targeted therapy was confirmed to increase overall survival by 10–20% in colorectal cancer. With the emergence of KRAS and BRAF mutations, resistance to EGFR-targeted therapy has developed, driven by mechanisms affecting both cellular pathways and the tumor microenvironment [ 44 ]. The kinase-activating mutations that result in enhanced EGFR tyrosine kinase activity might occur as a result of, or in addition to, anti-EGFR therapy [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…EGFR-targeted therapy was confirmed to increase overall survival by 10–20% in colorectal cancer. With the emergence of KRAS and BRAF mutations, resistance to EGFR-targeted therapy has developed, driven by mechanisms affecting both cellular pathways and the tumor microenvironment [ 44 ]. The kinase-activating mutations that result in enhanced EGFR tyrosine kinase activity might occur as a result of, or in addition to, anti-EGFR therapy [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…As the primary glucose transporter [14], GLUT1 supports glycolysis and mediates a complex series of tumor metabolism reprogramming events [15,16]. Several studies have suggested that GLUT1 may contribute to epidermal growth factor receptor tyrosine kinase inhibitor (EGFR-TKI) resistance by mediating glucose metabolism [17][18][19]. Clinical studies have reported a correlation between EGFR expression [20] and mutation status [21] with GLUT1 expression.…”
Section: Introductionmentioning
confidence: 99%
“…When cultured with mM doses of ascorbate, cancer cells with mutations in KRAS, and BRAF were demonstrated to uptake DHA via GLUT1, which was linked to a reduction in cell survival [ 8 ]. Furthermore, by modifying several signaling pathways, lowering important checkpoints, obstructing anaerobic glycolysis and angiogenesis, and upsetting their Warburg metabolism, while also preserving the health of colon cells [ 9 ]. Concurrent vitamin C delivery also has been shown to significantly alleviate chemotherapy-related side effects like constipation, sleeplessness, and exhaustion [ 3 ].…”
mentioning
confidence: 99%